Study of metallophthalocyanines attached onto pre-modified gold surfaces - Mashazi, Philani Nkosinathi (Rhodes University, Faculty of Science, Department of Chemistry, 2007)
Tetra-carboxy acid chloride phthalocyanine complexes of cobalt, iron and manganese were synthesized and characterized using spectroscopic and electrochemical techniques. These complexes were fabricated as thin films on gold electrode following a covalent immobilization and self-assembling methods. Surface electrochemical and spectroscopic characterization showed that these complexes are surface-confined species. The characterization using spectroscopic and electrochemical methods confirmed the formation of thiol and MPc SAMs on gold electrode. The electrocatalytic behaviour of the SAM modified gold electrodes was studied for the detection of L-cysteine and hydrogen peroxide. The limits of detection (LoD) for Lcysteine were of the orders of 10[superscript -7] mol.L[superscript -1] for all the MPc complexes studied and the LoD for hydrogen peroxide at cobalt phthalocyanine modified gold electrode was of the orders of 10[superscript -7]mol.L[superscript -1] for both electrocatalytic oxidation and reduction. The modification process for gold electrodes was reproducible and showed good stability, if stored in pH 4 phosphate buffer solutions and can be used over a long period of time. The cobalt phthalocyanine modified gold electrode was also investigated for the fabrication of glucose oxidase (GOx)-based biosensor and as an electron mediator between the enzyme and gold electrode. The behaviour of the enzyme modified gold electrode towards the detection of glucose was studied and the results gave a limit of detection of the orders of 10[superscript -6] mol.L[superscript -1] with low binding constant (4.8 mM) of enzyme (GOx) to substrate (glucose) referred to as Michaelis-Menten constant. The practical applications, i.e. the real sample analysis and interference studies, for the enzyme modified gold electrodes were investigated. These studies showed that the enzyme electrode is valuable and can be used for glucose detection.
Keywords: Phthalocyanines; Electrochemistry; Electrodes, Enzyme; Glucose -- Measurement